2019
DOI: 10.1111/rda.13438
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐145 regulates immune cytokines via targeting FSCN1 in Staphylococcus aureus‐induced mastitis in dairy cows

Abstract: Dairy cow mastitis is a detrimental factor in milk quality and food safety. Mastitis generally refers to inflammation caused by infection by pathogenic microorganisms. Our studies in recent years have revealed the role of miRNA regulation in Staphylococcus aureus‐induced mastitis. In the present study, we overexpressed and suppressed miR‐145 to investigate the function of miR‐145 in Mac‐T cells. Flow cytometry, ELISA and EdU staining were used to detect changes in the secretion of several Mac‐T cytokines and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…53 Chen et al revealed that miR-145 modulated immune cytokines by targeting fas-cin1 (FSCN1) in Staphylococcus aureus-induced mastitis in dairy cows. 54 Further studies will be needed to elucidate which signaling targets of miR-145-5p are involved in IFN induction during HTNV infection.…”
mentioning
confidence: 99%
“…53 Chen et al revealed that miR-145 modulated immune cytokines by targeting fas-cin1 (FSCN1) in Staphylococcus aureus-induced mastitis in dairy cows. 54 Further studies will be needed to elucidate which signaling targets of miR-145-5p are involved in IFN induction during HTNV infection.…”
mentioning
confidence: 99%
“…Previous studies have also shown that Bta-miR-145 expression was downregulated in udder tissues after S. aureus infection, consistent with our research. It was also found that overexpression of Bta-miR-145 significantly inhibited the proliferation of bMECs, and also reduced the secretion of IL-12 and TNF-α, but increased the secretion of IFN-γ (77). Therefore, the down-regulation of Bta-miR-145 is conducive to the production of IL-12 and TNF-α, thus inducing an immune response.…”
Section: Discussionmentioning
confidence: 90%
“…When calculating differences in gene expression, we used Htseq-count software to determine the number of gene reads in each sample. The estimate SizeFactors function in the DESeq R package was used to standardize the data, and the nbinomTest function was used to calculate the P-value and fold-change values in the difference comparisons (13). The condition used to screen differentially expressed genes was a P < 0.05 and multiple differences was more than 2 times.…”
Section: Gene Quantification Differential Gene Screening Functionalmentioning
confidence: 99%